Pengaruh Strategi Engagement Learning dalam Pembelajaran Agama Kristen terhadap Social Skills Siswa - Susanti, Lidia; Agustina, Selly (Institut Agama Kristen Negeri Toraja, 2023)
The existence of changes in the learning system before the pandemic, during the pandemic, and after the pandemic has brought disruption to education, affecting the innovation of learning using technology, social changes, and other external factors. Unexpectedly, this disruption has impacted the learning process in organizing lessons, accessing materials, and the delivery of lessons, emphasizing the creativity and innovation of teachers in providing education. The research aims to provide learning strategies that can engage students in interacting with peers, and teachers, and participating in learning materials to enhance students' social abilities. Social skills are essential for their future in interacting, communicating, and relating to others effectively in various situations. Students with social skills will be able to build positive relationships with others, collaborate, and create a pleasant environment. The research method is quantitative with an intact group comparison design, and the research sample consists of 74 students. The results of the study show that the t-value of 9.130 is greater than the t-table value of 1.677, meaning that there is an influence of using engagement learning strategies on the social skills of students. From the R Square value, it is obtained that 0.639 or 63.9%, indicating that the use of engagement learning strategies has a 63.9% influence on the social skills of students. Christian religious education needs to use engagement learning strategies to improve the social skills of Christian students. Keywords: engagement learning; social skills